Geometric model for 3D through-thickness orthogonal interlock composites. (January 2015) - Isart, N.; Mayugo, J.A.; Blanco, N.; Ripoll, L.; Solà, A.; Soler, M.
Abstract: The elastic properties of 3D through-thickness orthogonal interlock composite materials are affected by the curvature of the yarns caused by compaction during the manufacturing process. However, most of the models in the literature do not take into account this fact resulting in not so accurate predictions. A novel geometric model accounting for the compaction and curvature effects on the cross-section and distribution of fill and warp yarns in 3D through-thickness orthogonal interlock composite materials is presented in this work. The model assumes sinusoidal functions to represent the curvature along the length of the fill and warp yarns due to binder. Then, with only a set of preform parameters combined with few geometric measurements in optical micrographs of specific sections the geometry of the material can be fully determined. The model is compared and validated with the real geometry and fibre area fraction of the warp and fill yarns of a 3D through-thickness orthogonal interlock carbon/epoxy composite and the predictions of an analytical model present in the literature. After the comparison, it can be concluded that the model is a useful tool to describe the real geometry and can be used with finite element analyses to obtain its elastic properties.